Testing the feasibility of coral nurseries in an upwelling area in the North Pacific of Costa Rica - Fabregat-Malé, Sònia; Mena-González, Sebastián; Quesada-Perez, Fabio; Alvarado, Juan José (Frontiers in Marine Science, 2024)
The decline of coral reefs has increased interest in ecological restoration. Due to the scarcity of coral gardening projects in the Eastern Tropical Pacific, improving our understanding of such techniques is key. We report the results of coral gardening using the branching Pocillopora spp. and massive coral species (Pavona gigantea, Pavona clavus and Porites lobata) in an upwelling area in Costa Rica. We examined whether nursery type influenced Pocillopora spp. survival and growth, and how environmental conditions shaped restoration. We monitored the survival and growth of Pocillopora spp. fragments (n = 334) and microfragments of massive species (P. gigantea [n = 148], P. clavus [n = 37], P. lobata [n = 66]) over 11 months. Survival at the end of the gardening period was 51% for Pocillopora spp., 59% for P. clavus, 55% for P. gigantea, and 17% for P. lobata, with a decline after a cease in maintenance caused by the COVID-19 lockdown. Pocillopora spp. fragments in the floating nurseries exhibited higher growth (7.52 ± 1.98 and 6.64 ± 2.91 cm yr-1) than in the A-frame (4.16 ± 2.35 cm yr-1), which suggests the benefits of suspending fragments. For massive microfragments coral growth was 1.92-4.66 cm2 yr-1 and were affected by pigmentation loss, causing partial tissue loss and mortality. Our results point towards acclimation to local conditions, and show the need to develop site-specific cost-efficient gardening techniques for massive species, allowing for a multi-species approach to ensure long-term ecosystem recovery.